2015
DOI: 10.1111/jphp.12449
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian green propolis induced apoptosis in human lung cancer A549 cells through mitochondrial-mediated pathway

Abstract: Although propolis induces apoptosis mainly by p53-independent manner, it may be induced by another pathway, and new insights may arise for preventing or treating lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 48 publications
4
31
0
1
Order By: Relevance
“…It is well known that apoptosis and cell cycle deregulation are closely related events; however, disruption of cell cycle progression may lead to apoptotic/necrotic death, suggesting that both types of cell death may be useful in cancer therapy . Our results are in agreement with previous investigation showing that Brazilian green propolis inhibited different cancer cells by inducing apoptosis …”
Section: Discussionsupporting
confidence: 92%
“…It is well known that apoptosis and cell cycle deregulation are closely related events; however, disruption of cell cycle progression may lead to apoptotic/necrotic death, suggesting that both types of cell death may be useful in cancer therapy . Our results are in agreement with previous investigation showing that Brazilian green propolis inhibited different cancer cells by inducing apoptosis …”
Section: Discussionsupporting
confidence: 92%
“…Apoptosis is one of important mechanisms by which various agents exhibit their anticancer effects . In this study, the apoptosis‐inducing effect of luteolin on CCA cells was observed by the fluorescent dye AO/EB staining and flow cytometry with annexin V/PI staining.…”
Section: Discussionmentioning
confidence: 96%
“…There are several studies indicating apoptotic effect of propolis from various origins on various cancer cell lines. [2,3,17] In one of these studies published by Frión-Herrera et. al., authors revealed that Brazilian green propolis induced apoptosis via a p53-independent way on A549 cells.…”
Section: Protein Expression Analysismentioning
confidence: 99%
“…[1] Among these bioactivities, cytotoxic and anticancer activities of propolis have particularly attracted much attention in recent years. [2][3][4][5] Carcinogenesis is a multistage process; involving initiation, promotion and progression. During cell division, maintenance of tissue homeostasis, integrity of nuclear material and cell size in under control of cell cycle checkpoints.…”
Section: Introductionmentioning
confidence: 99%